Procesos cognitivos en el aprendizaje de los estudiantes con discapacidad intelectual del bachillerato general unificado - García Erazo, Pilar del Rocío (2021)
This research aimed to determine the cognitive processes involved in the learning of students with intellectual disabilities of the General Unified High School (BGU) of the Educational Unit "Vicente Anda Aguirre" in the Canton Milagro, Guayas, Ecuador. This research is based on a methodological design of a non-experimental type, with a qualitative-quantitative approach, of a descriptive, documentary and field type, using the techniques of the interview, the survey, and the classroom observation sheet. The documentary review establishes that the degree of intellectual disability that students present ranges from moderate to mild, and they need curricular adaptations, mostly grade 2 and grade 3, in addition, they present other difficulties such as hearing and behavior problems........